Inovasi Preventif Terhadap Perilaku Bullying: Pengembangan Modul Bimbingan Kelompok di SMA - Arliady; Saman, Abdul; Sinring, Abdullah (Universitas Palangka Raya, 2024)
Bullying in schools is a serious issue that impacts students' well-being. Addressing this problem effectively requires innovative preventive approaches. This study aims to develop and test the effectiveness of a group guidance module designed to prevent bullying behavior in high schools. The research employed a Research and Development (R&D) method based on the modified Borg and Gall model, encompassing needs analysis, planning and development, expert validation, and small group trials. Data were collected through observations, interviews, and questionnaires at UPT SMAN 1 Pangkep. The results indicate that the developed module was rated highly suitable by experts, with an average feasibility score above 80%. Small group trials demonstrated the module's effectiveness in raising students' awareness of bullying and promoting positive behaviors. Overall, the module was well-received by students and teachers as a preventive tool for addressing bullying. In conclusion, this group guidance module proved to be effective and can be implemented to create a safe and conducive learning environment, enhancing students' social skills in preventing and addressing bullying.